Optimization of BI solution for project management and capacity planning - Constantinov, Daria; Stanovská, Iva; Smolníková, Markéta; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
In today’s business environment, effective project management relies on a data-driven decision-making process. As organizations collect a wide range of data, its interpretation and visualization must be conducted effectively. This thesis aims to optimize and improve an existing BI solution, whose main purpose is to support the selected consulting firm in its decision-making process related to project management and employee capacity planning. The best practices in data visualization and data storytelling are used to present the information in the best possible way. The existing BI solution is optimized by automating the ETL process and extended with new visuals using data storytelling. The thesis examines the effect of implementing data storytelling and data visualization best practices on the decision-making process in the selected team. This relationship is studied based on the conducted questionnaire survey. The results of this questionnaire support the original hypothesis that the decision-making process becomes more effective when best practices in data visualization and storytelling are used.
Vedoucí práce: Iva Stanovská
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses